Understanding Green Product Purchase Intentions Using the Theory of Planned Behavior: Case study of Algerian Consumers’ - Sidi Mohammed Benachenhou; Imene Dali Youcef; Salah Hamouti (International Journal of Business and Development Studies)
Objective: Consumers have recently become more concerned about environmental protection and have turned to eco-friendly products, also known as green products. To explore the factors that determine consumers’ green product purchase intentions, this study aims to measure the effects of TPB variables (e.g., perceived behavioural control, attitude, and subjective norms) on green product purchase intentions. Through this study, we build a theoretical framework that combines the ideas and perspectives of previous studies on sustainable consumption.Methods: In order to validate our research hypotheses, questionnaires were used to collect primary data from a sample of 219 participants in Algeria. Therefore, this research uses quantitative study method to design the research model which was tested using structural equation modeling (SEM) method. We analyzed the statistical data using SPSS v22.0 and Statistica v08.Results: The results show that purchasing intention of green products is positively affected by attitude (ATT), subjective norms (SN), and perceived behavior control (PBC). Furthermore, our findings discovered that the influence of PBC on intention to purchase green products was more significant than the effects of SN and ATT, enhancing our understanding of the key drivers of green product purchase intentions.Conclusion: These ﬁndings can generate more suitable managerial implications and policy contributions to promote green product consumption. It also highlights the key factors determining consumers’ eco-friendly purchasing intentions in Algeria. Therefore, identifying and understanding these factors enables the organization to develop effective strategies that guide consumers towards sustainable consumption and mitigate the negative repercussions of environmentally harmful consumption.